New Design of Raskin Program (Analysis of the RASDA Implementation in Kulonprogo Regency) - Raden Rahman Asjhatri Fandaru (Magister Ilmu Administrasi Publik, 2016)
This thesis is an analysis of public policies based on the research carried out about the implementation of RASDA Program (local rice husbandry) in Kulonprogo in 2015. It is claimed as a new alternative offered to replace the Government RASKIN Program that is already running. This research aimed at determining how effective the implementation of the RASDA Program in Kulonprogo was and identifying the factors that cause RASDA program did not run as the expectation. The method used in this study was a qualitative method using two types of data, primary and secondary data. The data collection techniques used were observation, interview, and documentation with informants selection technique using the principle of purposive and snowball techniques. The data analysis technique was done through data reduction, data display, and data verification.The results showed that efforts to renew the RASKIN Program (cheap-priced rice) through RASDA program were not successfully done. The achievement of program outputs and outcome indicators were still far away from the expectation. The progress was not significantly improved, it still encountered the same problems as those in the implementation of the previous RASKIN Program. Meanwhile, farmers did not have any benefits from the uptake of the local rice because it was not optimally prepared.There are several factors that cause RASDA Program in Kulonprogro did not run well. The first reason was that it is difficult to link the concept of the program with the actual situation, seen from: (1) the farmers as the program target still thought conservatively causing the loss of the benefits that will be gained from the RASDA Program; (2) the intervention of political elites in the process of policy formulation; (3) the limited authority of the local government in the National RASKIN Program; and (4) the incoherence among the needs for resources in the factual conditions. The second cause, the conflict of interest among the holders cause the program implementation did not synchronize to each other, as seen from: (1) their efforts to make RASDA program as a springboard for “other” purposes; (2) the bias support of BULOG; (3) the lack of enthusiasm and initiatives among the holders/bureaucracy; and (4) the entrepreneurs’ mindset of business that dominated farmers community. The third reason is that there was not awareness on the characteristics of the group target to anticipate problems that arise.Based on these findings, the researcher suggested the government focus in optimizing the current mechanisms of the food subsidies. The government should also concern in looking for other alternatives to optimize the potential of the local foods. The government should also do some efforts to gain the welfare for farmers, by: (1) reconstructing values and norms in terms of social rules to support the program with the intensive socialization; (2) allocating the budget the APBD for the procurement of subsidized rice for poor households who are not registered; (3) monitoring the program up to the lowest level intensively; (4) encouraging small entrepreneurs to become BULOG’s partners to seek an access to the Capital; (5) maintaining fair competition among rice traders; (6) conducting studies on the possibility of establishing an integrated rice husbandry regional company; (7) encouraging the local rice branding.